Study About Pathogenic Bacteria Associated With Bovine Mastitis - Safana A. S. AL-Taan; Asmaa H. AL-Jobori; Anton S. AL-Bana. (The Iraqi Journal of Veterinary Medicine, 2004)
Out of 100 raw milk samples collected from one hundred cows infected with mastitis, thirty three isolates of different types of pathogenic bacteria were isolated using different types of selective media.